Microemulsions as delivery systems of lemon oil and β‐carotene into beverages: stability test under different light conditions. (31st August 2019) - Calligaris, Sonia; Manzocco, Lara; Valoppi, Fabio; Comuzzo, Piergiorgio; Nicoli, Maria Cristina
Abstract: BACKGROUND: Microemulsions have been proposed as delivery systems for different lipophilic substances in transparent water‐based systems. The chemical stability of the delivered compounds is a key factor to broaden the application of microemulsions in the food sector. The stability of a model beverage containing a microemulsion delivering β‐carotene and lemon oil was tested under increasing light intensity up to 6000 lx at 20 °C. RESULTS: The transparent microemulsion resulted physically stable during storage indicating that no coalescence phenomenon occurred. On the contrary, both colour and flavour of the microemulsion degraded as a consequence of limonene and β‐carotene oxidation. Kinetic data obtained at increasing light intensity were used to estimate the light dependence of beverage spoilage and the mathematical relationship obtained was used to predict spoilage rate under different light conditions. Finally, a shelf life predictive model was proposed. CONCLUSIONS: Transparent microemulsions can be successfully used to deliver flavoured oil and colourants into beverages. However, the photostability of the delivered compounds should be carefully studied to estimate product shelf life. To this aim, the availability of models predicting shelf life as a function of enlightening conditions could largely contribute to speed up the process. © 2019 Society of Chemical Industry